Layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields, its preparation method, and its application in photocatalytic hydrogen production.

CN122912880APending Publication Date: 2026-10-16QIQIHAR UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611377969.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该过程会牺牲催化剂优异的还原或氧化热力学电势

Benefits of technology

1.本发明采用WO3, WS2, ZnIn2S4依次复合构筑串联内建电场,实现光电子的长程单向转移,避免因载流子快速复合,使光生电子能用于光催化产氢过程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912880A_ABST
    Figure CN122912880A_ABST
Patent Text Reader

Abstract

The application discloses a layered ZnIn2S4 / WO3 / WS2 heterojunction with a double built-in electric field, a preparation method of the heterojunction and application of the heterojunction in photocatalytic hydrogen production, and belongs to the field of photocatalytic semiconductor materials. The heterojunction comprises a layered WO3 / WS2 carrier and ZnIn2S4 loaded on the surface of the layered WO3 / WS2 carrier, and the layered WO3 / WS2 carrier comprises a layered WS2 substrate and WO3 formed in situ on the surface of the layered WS2 substrate. In the application, WS2 with a Fermi level slightly lower than that of ZnIn2S4 is first compounded with WO3, and then ZnIn2S4 is grown on the surface of the WO3 / WS2, so that the energy level difference is gradually reduced through a stepped complementary energy band structure, the intrinsic reduction potential of ZnIn2S4 is maintained, and the photocatalytic reduction H2 thermodynamic potential of the heterojunction material is improved. In addition, a series of built-in electric fields are constructed based on the WO3, WS2 and ZnIn2S4 in sequence, long-range one-way transfer of photoelectrons is realized, and the photoelectrons can be used in the photocatalytic hydrogen production process by avoiding the rapid recombination of carriers. The heterojunction prepared by the application has good structural stability and recycling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic semiconductor materials, specifically to a layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields, its preparation method, and its application in photocatalytic hydrogen production. Background Technology

[0002] Photocatalytic water splitting for hydrogen production can directly convert solar energy into storable clean chemical fuels, providing a sustainable solution to the dual crises of energy shortage and environmental degradation. However, traditional single-component photocatalysts cannot simultaneously achieve broad-spectrum light absorption, efficient charge separation, and long-term structural stability, resulting in actual hydrogen production efficiency far lower than theoretical values, which greatly restricts their industrial application.

[0003] Zinc indium sulfide (ZnIn2S4), a typical two-dimensional layered metal chalcogenide, has a narrow band gap of 2.3–2.6 eV, allowing for efficient utilization of visible light. Its conduction band potential is approximately -0.75 V relative to the standard hydrogen electrode, thermodynamically meeting the requirements for hydrogen ion reduction. + The standard electrode potential for H2 is 0.15 V. The excellent optical and electrochemical properties of ZnIn2S4 make it a highly promising and competitive visible-light-driven photocatalytic material for water splitting to produce hydrogen. However, inherent structural defects in pure-phase ZnIn2S4 severely limit its photocatalytic performance: weak van der Waals forces between adjacent ZnIn2S4 nanosheets hinder interlayer charge transport, shorten the migration distance of photogenerated carriers, and exacerbate bulk recombination of electron-hole pairs; simultaneously, insufficient exposure of active sites on the material surface leads to sluggish interfacial reaction kinetics, further resulting in poor hydrogen production activity and hindering its practical application in photocatalysis.

[0004] To address these issues, researchers have developed various modification strategies, including morphology and phase control, heteroatom doping, co-catalyst loading, defect engineering, and heterostructure construction. Heterostructure construction is considered one of the most effective modification strategies. This method can rationally control bandgap matching, achieving directional spatial separation of charge carriers and significantly improving photocatalytic hydrogen production performance. Combining ZnIn2S4 with other semiconductors can construct heterostructures with controllable bandgap structures, significantly accelerating the spatial separation and long-distance migration of photogenerated electron-hole pairs, and alleviating the severe bulk carrier recombination problem caused by weak interlayer van der Waals forces and hindered interlayer charge transport in pure-phase ZnIn2S4. Although binary ZnIn2S4-based heterojunctions can improve inherent material defects to some extent, significant shortcomings still exist: (1) The built-in electric field driving force generated by a single heterogeneous interface is insufficient, and the semiconductor properties of the catalyst make it difficult to achieve long-range transfer of photogenerated electrons. This results in photogenerated electrons and holes being close to each other and attracting each other to recombine.

[0005] (2) During the formation of the semiconductor structure, the semiconductors will bond tightly together. Due to the difference in Fermi levels, electron transfer will occur between the semiconductors until the Fermi levels are aligned. This process will sacrifice the excellent reduction or oxidation thermodynamic potential of the catalyst.

[0006] (3) The core limitation of binary heterojunctions stems from the inherent optical property barrier of the two-component composite system. This type of heterojunction relies solely on the intrinsic light absorption characteristics of indium zinc sulfide and a single auxiliary component to form a complementary absorption effect. The light response bands of the two components are fixed and have a narrow coverage range. The superposition effect of spectral complementarity is very limited, and it can only cover a small band in the visible light region, making it impossible to achieve efficient utilization of broad-spectrum visible light.

[0007] (4) The charge transfer channels of conventional binary heterojunctions are imperfect, resulting in low separation efficiency and high recombination rate of photogenerated carriers. A large number of holes remain on the surface of zinc indium sulfide and continue to accumulate, further aggravating the local photocorrosion reaction.

[0008] Due to the shortcomings of binary ZnIn2S4-based heterojunctions, ternary ZnIn2S4-based heterojunctions have also been studied and prepared in the prior art. However, due to defects in the preparation process, the structure of ternary ZnIn2S4-based heterojunctions is unstable. Summary of the Invention

[0009] Based on the problems existing in the prior art, the present invention provides a layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields, its preparation method and its application in photocatalytic hydrogen production. The product prepared by the present invention has good structural stability, catalytic activity and recyclability.

[0010] To achieve the objectives of this invention, the following technical solution is adopted: The first aspect of this invention is to provide a layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields, comprising a layered WO3 / WS2 carrier and ZnIn2S4 loaded on the surface of the layered WO3 / WS2 carrier. The layered WO3 / WS2 carrier includes a layered WS2 substrate and WO3 formed in situ on the surface of the layered WS2 substrate. The layered ZnIn2S4 / WO3 / WS2 heterojunction provided by this invention has the following structural features: First, this invention employs a series-connected built-in electric field constructed by sequentially combining WO3, WS2, and ZnIn2S4. Due to electron rearrangement and Fermi level alignment after material recombination, at the WS2-ZnIn2S4 interface, electrons decrease on the ZnIn2S4 side, resulting in a positive charge, while electrons accumulate on the WS2 side, resulting in a negative charge, thus constructing the first built-in electric field. Similarly, at the WO3-WS2 interface, electrons decrease on the WS2 side, resulting in a positive charge, while electrons accumulate on the WO3 side, resulting in a negative charge, thus constructing the second built-in electric field. This series-connected electric field enables long-range unidirectional, stepwise electron transfer from WO3 to WS2 to ZnIn2S4, reducing the attraction of intrinsic holes to photogenerated electrons. This allows more of the absorbed photon energy to be converted into effective charge carriers to participate in the catalytic reaction, avoiding the waste of light energy caused by rapid carrier recombination. By comparing the charge separation efficiency and recombination of single-component, binary heterojunction, and ternary composite materials using transient photocurrent and photocurrent polarization (PL), the synergistic enhancement effect of dual built-in electric fields on photocurrent transfer and suppression of photogenerated carrier recombination was confirmed. Combined with DFT theory calculation of interface charge differential density, the charge transfer direction and the formation mechanism of built-in electric field were revealed at the atomic level.

[0011] Secondly, this invention reduces the energy level gap step by step through a stepped complementary band structure. First, WS2, with a Fermi level slightly lower than ZnIn2S4, is composited with WO3, which has a lower Fermi level. Then, ZnIn2S4 is grown on the WO3 / WS2 surface, maximizing the preservation of the intrinsic reduction potential of ZnIn2S4 and increasing the thermodynamic potential for photocatalytic reduction of H2 in the heterojunction material. Simultaneously, ZnIn2S4, WO3, and WS2 achieve full spectral coverage across multiple bands—ultraviolet, short-to-mid-visible, and long-visible / near-infrared—through their differentiated band gaps. Energy level matching is achieved through a stepped, staggered band structure, directly broadening the material's optical absorption spectrum at the physical level.

[0012] Finally, the ternary system constructed in this invention rapidly removes corrosive holes from the surface of indium sulfide (ISS) through band structure, reduces carrier recombination through multi-level interfaces, stabilizes the crystal framework through a coating structure, and consumes oxidizing holes using two auxiliary materials. These multiple effects collectively block the reaction pathway of sulfide photocorrosion, significantly improving the structural stability and recyclability of the material.

[0013] A second aspect of the present invention is to provide a method for preparing a ZnIn2S4 / WO3 / WS2 heterojunction as described above, comprising the following steps: Step 1: Take a certain mass of WS2 powder and place it in a crucible, then place it in a muffle furnace and heat at 4.0 ℃·min. -1The heating rate was raised to 280-320 ℃, and the samples were calcined at a constant temperature for 2.0 h. By controlling the calcination process, WS2 was partially oxidized and transformed into WO3, while avoiding excessive oxidation of WS2, thus obtaining WO3 / WS2 precursor. After the samples were naturally cooled to room temperature in the furnace, they were placed in an agate mortar and ground thoroughly until fine to obtain uniform precursor powder.

[0014] Step 2: Prepare a mixed solvent of glycerol and deionized water at a ratio of 1:3 to 1:5. Add the precursor powder to the mixed solution at a mass percentage of 0.5% to 1.25%. Disperse the mixture ultrasonically at room temperature for 0.5 to 2.0 hours to obtain a uniform dispersion. The purpose of ultrasonic dispersion is to ensure sufficient dispersion of the precursor, which is beneficial for subsequent complexation with ZnIn2S4. However, excessive ultrasonication should be avoided to prevent problems such as peeling of the WS2 thin layer and structural damage.

[0015] Step 3: Add zinc chloride (0.15%~0.20%), indium chloride tetrahydrate (0.20%~0.80%), and thioacetamide (TAA) to the dispersion in sequence, and stir magnetically for 0.5 h to obtain a homogeneous precursor mixture.

[0016] Step 4: The prepared precursor mixture is stirred in an oil bath at 75~90 ℃ for 1.5~3 h to obtain a ZnIn2S4 / WO3 / WS2 catalyst suspension.

[0017] Step 5: Centrifuge the turbid liquid for 0.5 h and collect the bottom precipitate; wash the precipitate three times with anhydrous ethanol and deionized water alternately, and dry the washed sample in a vacuum drying oven at 60 ℃ for 12 h to finally obtain a ZnIn2S4 / WO3 / WS2 photocatalyst with dual built-in electric fields, with a ZnIn2S4 mass fraction of 10%~50%.

[0018] In step 1, when the calcination temperature is below 280℃, the activation energy for WS2 oxidation cannot be met, resulting in only a small amount of weak oxidation of the surface lamellar layers. The product is mainly amorphous, low-oxidation-state tungsten oxide, with a large amount of WS2 inside remaining unreacted. This not only makes it difficult to form a tightly bonded heterogeneous interface between crystalline WO3 and WS2, but also introduces disordered lattice defects, leading to increased carrier recombination and bandgap imbalance. This fails to achieve the design goals of broadening light absorption and suppressing ZnIn2S4 photocorrosion, and the product phase composition varies greatly from batch to batch, resulting in poor experimental repeatability. When the calcination temperature is above 320℃, WS2 undergoes deep oxidation, with a large amount of layered substrate being converted into WO3, and the two-dimensional lamellar structure breaking down and sintering. At the same time, WO3 grains coarsen and the concentration of interface defects increases, which not only reduces long-wavelength light absorption but also accelerates photogenerated carrier recombination. Furthermore, high-temperature oxidation causes powder pore collapse and reduces active interfaces, ultimately weakening the heterojunction's ability to separate charges and suppress photocorrosion, resulting in a decrease in the overall photocatalytic activity and cycle stability of the material. Therefore, the calcination temperature needs to be strictly controlled within the range of 280-320 ℃ during the preparation process.

[0019] In step 2, a solvent composed of glycerol and deionized water is used. Glycerol adjusts the viscosity and surface energy of the system, inhibiting the sedimentation and agglomeration of WO3 / WS2 powder and achieving uniform and stable powder dispersion. Simultaneously, glycerol slows down the hydrolysis rate of thioacetamide, inducing heterogeneous nucleation of ZnIn2S4 on the WO3 / WS2 surface, forming a tightly bound multi-level heterogeneous interface. When the volume ratio of glycerol to deionized water is greater than 1:5, insufficient system viscosity occurs, leading to the following problems: WO3 / WS2 sedimentation and stratification; weakened complexing ability, excessive nucleation and agglomeration of ZnIn2S4, making heterojunction formation difficult and weakening the dual built-in electric field; and decreased crystallinity, increased carrier recombination rate, and deteriorated photocatalytic performance. When the volume ratio of glycerol to deionized water is less than 1:3, the excessive glycerol makes the system too viscous, leading to the following problems: difficulty in stirring and ultrasonic mass transfer, resulting in uneven local concentration; excessive slow release of metal ions, resulting in fewer nuclei, coarser grains, and a decrease in specific surface area; difficulty in removing glycerol during washing, and it still covers active sites after vacuum drying; and increased difficulty in centrifugation, with impurities entrained in the product, leading to reduced purity. Therefore, controlling the glycerol / water volume ratio within the range of 1:3 to 1:5 ensures good dispersion, uniform nucleation, and a clean surface, thereby optimizing the heterojunction interface and improving photocatalytic performance.

[0020] In step 4, when the oil bath temperature is below 75℃, TAA hydrolysis is slower, and the system S 2-Insufficient concentration hinders complete precipitation of metal ions, leading to metal ion residue and reduced ZIS yield. Simultaneously, the low number of crystal nuclei, poor crystallinity, and disordered defects make it difficult for ZnIn2S4 to be uniformly anchored on the WO3 / WS2 surface. When the oil bath temperature exceeds 90℃, TAA decomposes upon heating, releasing H2S, resulting in homogeneous nucleation and coarse, heavily aggregated ZnIn2S4 particles. Furthermore, air bubbles impact the support, causing the grown ZnIn2S4 to detach from the WO3 / WS2 surface, disrupting the composite structure. Excessively high temperatures can also cause glycerol oxidation and carbonization, producing organic carbon impurities that cover active sites, affecting product performance. In addition, controlling the reaction time to 1.5–3 h allows for sufficient contact at the heterojunction interface for composite formation, improving the stability of the product structure and its photocatalytic activity.

[0021] The photocatalyst prepared in this invention requires a ZnIn2S4 mass fraction of 10%–50%. When the ZnIn2S4 mass fraction is less than 10%, the ZnIn2S4 nanosheets have insufficient coverage on the WO3 / WS2 support, resulting in a small number of heterojunction interfaces and difficulty in forming a continuous dual built-in electric field. Since WO3 / WS2 primarily absorbs ultraviolet and near-ultraviolet light, its visible light response is weak, leading to poor visible light capture ability and a low total number of photogenerated carriers under low ZnIn2S4 loading. Furthermore, the insufficient number of interfacial barriers prevents effective separation of photogenerated electrons and holes, resulting in a high recombination rate. Simultaneously, the lack of a ZnIn2S4 protective layer leads to the oxidation of WS2 and WO3 by holes under illumination, resulting in poor material cycle stability. When the ZnIn2S4 mass fraction is greater than 50%, the excessive ZnIn2S4 coats the WO3 / WS2 support, resulting in lamellar stacking and aggregation, a decrease in specific surface area, and some ZnIn2S4 becoming free and nucleating on its own, only acting as a mixture and not forming heterojunctions with the support. The excessively thick ZnIn2S4 lamellars cause light scattering and internal shading, leading to a decrease in effective light utilization. In addition, the insufficient proportion of WO3 / WS2 results in a lack of electron trapping sites, a weakened built-in electric field, and a decline in charge separation efficiency. The active sites are buried, charge recombination is aggravated, and the accumulation of electrons inside ZnIn2S4 promotes the generation of sulfur vacancies, exacerbating photocorrosion. After multiple cycles, the structure breaks down and the activity rapidly declines.

[0022] A third aspect of the present invention is to provide a layered ZnIn2S4 / WO3 / WS2 heterojunction as described above as a catalyst for photocatalytic water splitting to produce hydrogen, wherein the heterojunction has good catalytic performance and cycling performance.

[0023] The present invention has the following beneficial effects: 1. This invention uses WO3, WS2, and ZnIn2S4 to construct a series built-in electric field, thereby realizing long-range unidirectional transfer of photoelectrons and avoiding rapid recombination of charge carriers, so that the photogenerated electrons can be used in the photocatalytic hydrogen production process.

[0024] 2. This invention improves the thermodynamic potential of photocatalytic reduction of H2 by gradually reducing the energy level difference through a stepped complementary band structure, maintaining the intrinsic reduction potential of ZnIn2S4.

[0025] 3. This invention achieves full coverage of the ultraviolet, short-to-medium visible light, and long visible light / near-infrared multi-band spectra by differentiating the band gap widths of ZnIn2S4, WO3, and WS2, thus broadening the light absorption spectrum range of the material.

[0026] 4. The ternary system constructed in this invention rapidly removes corrosive holes from the surface of indium sulfide (ISS) through band arrangement, stabilizes the crystal framework with a coating structure, and consumes oxidizing holes using two auxiliary materials. These multiple effects collectively block sulfide photocorrosion, significantly improving the structural stability and recyclability of the material. Attached Figure Description

[0027] Figure 1 The XRD patterns of the ZnIn2S4 / WO3 / WS2 heterojunctions prepared in Examples 1, 2, and 3 are shown below. Figure 2 Scanning electron microscope image of the layered WO3 / WS2 carrier prepared in Example 1; Figure 3 Scanning image of the ZnIn2S4 / WO3 / WS2 photocatalyst prepared in Example 1; Figure 4 Transmission image of the ZnIn2S4 / WO3 / WS2 photocatalyst prepared in Example 1; Figure 5 XPS images of the products prepared in Example 1 and the comparative example; Figure 6 The graph shows the photocatalytic hydrogen production performance of the products prepared in each embodiment and comparative example; Figure 7 Cyclic performance testing of the ZnIn2S4 / WO3 / WS2 photocatalyst prepared in Example 1; Figure 8 Nitrogen adsorption-desorption of the products prepared for the examples and comparative examples; Figure 9 The pore size distribution diagrams are for the products prepared in Example 1 and the comparative example. Figure 10 The UV-Vis diffuse reflectance spectra of the products prepared in Example 1 and the comparative example are shown. Figure 11 EIS diagrams of the products prepared in Example 1 and the comparative example; Figure 12 PL plots of the products prepared in Example 1 and the comparative example; Figure 13 Transient photocurrent plots of the products prepared in Example 1 and the comparative example; Figure 14 This is a schematic diagram of the dual built-in series electric field and long-range photoelectron transfer of the ZnIn2S4 / WO3 / WS2 photocatalysts prepared in Examples 1, 2, and 3. Detailed Implementation

[0028] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0029] Example 1: Step 1: Take a certain mass of WS2 powder and place it in a crucible, then place it in a muffle furnace and heat at 4.0 ℃·min. -1 The temperature was increased to 300 °C at a heating rate and calcined at a constant temperature for 2.0 h. After the sample cooled naturally to room temperature in the furnace, it was placed in an agate mortar and ground thoroughly until fine to obtain a uniform layered WO3 / WS2 carrier powder, which was labeled as WO3 / WS2-300.

[0030] Step 2: Prepare a mixed solvent of glycerol and deionized water at a ratio of 1:4. Add WO3 / WS2 carrier powder to the mixed solvent at a mass percentage of 0.57% and ultrasonically disperse at room temperature for 0.5 h to obtain a uniform dispersion.

[0031] Step 3: Add zinc chloride (0.183%), indium chloride tetrahydrate (0.594%), and thioacetamide (0.501%) by mass percentage sequentially to the dispersion, and stir magnetically for 0.5 hours to obtain a homogeneous precursor mixture.

[0032] Step 4: The prepared precursor mixture was stirred and reacted in an oil bath at 80°C for 2 h to obtain a ZnIn2S4 / WO3 / WS2 suspension.

[0033] Step 5: Centrifuge the suspension for 0.5 h and collect the bottom precipitate; wash the precipitate three times with anhydrous ethanol and deionized water alternately, and dry the washed sample in a vacuum drying oven at 60 ℃ for 12 h to finally obtain a layered ZnIn2S4 / WO3 / WS2 heterojunction photocatalyst with dual built-in electric fields, labeled as ZnIn2S4 / WO3 / WS2-300.

[0034] In this embodiment, the catalyst structure contains 43.50% ZnIn2S4 by mass, with ZnIn2S4 uniformly coating the WO3 / WS2 surface, forming a complete and continuous heterojunction interface. The three phases are in close contact, forming a complete multi-level dual built-in electric field. In this embodiment, a ZnIn2S4 / WO3 / WS2 photocatalyst was prepared by sequentially adding 0.183% zinc chloride, 0.594% indium chloride tetrahydrate, and 0.501% thioacetamide by mass percentage to the dispersion. The atomic ratio of Zn, In, and S is 1:2:4, which is a typical indium thiosulfate zinc structure.

[0035] Example 2: Compared with Example 1, the difference in this example is that in step 1, the temperature is 4.0 °C·min. -1 The heating rate was increased to 280 °C, and the product was calcined at this temperature for 2.0 h. All other processes were the same as in Example 1. The product prepared in this example was labeled as ZnIn2S4 / WO3 / WS2-280.

[0036] The ZnIn2S4 / WO3 / WS2 photocatalyst prepared in this embodiment has a small amount of oxidation on the surface of WS2, with WS2 as the main component and low WO3 formation, low crystallinity, and a thin oxide layer. The WS2 layered framework is intact, with almost no breakage of the sheets. The WO3 is mostly amorphous / small crystallites, and the heterostructure interface is thin. The prepared ZnIn2S4 / WO3 / WS2 photocatalyst has the highest WS2 retention. The narrow bandgap layered WS2 can efficiently capture long-wavelength visible light of 550~800 nm, broadening the light absorption window of the ternary system and improving the utilization rate of sunlight. The intact two-dimensional WS2 serves as a conductive substrate, acting as an electron reservoir, rapidly extracting electrons from the conduction band of ZnIn2S4, and suppressing carrier recombination to a certain extent. The sheet specific surface area is large: the intact WS2 framework can load more ZnIn2S4 nanosheets, exposing hydrogen production active sites.

[0037] Example 3: Compared with Example 1, the difference in this example is that in step 1, the temperature is 4.0 °C·min. -1 The heating rate was increased to 320 °C, and the product was calcined at this temperature for 2.0 h. All other processes were the same as in Example 1. The product prepared in this example was labeled ZnIn2S4 / WO3 / WS2-320.

[0038] The ZnIn2S4 / WO3 / WS2 photocatalyst prepared in this embodiment undergoes high-temperature deep oxidation, resulting in the conversion of a large amount of WS2 into WO3, and the WO3 grains sinter and grow. Some WS2 sheets break and collapse, forming WO3 particle clusters. The prepared ZnIn2S4 / WO3 / WS2 photocatalyst, with its high content and high crystallinity of WO3, possesses extremely strong hole-trapping ability, outstanding instantaneous inhibition of photocorrosion, and rapid hole oxidation and consumption rate. It exhibits the strongest absorption in ultraviolet / short-wave visible light: with the highest WO3 content, it has the best ability to trap ultraviolet and short-wave visible light below 480 nm.

[0039] Comparative Example 1: Preparation of ZnIn2S4 catalyst A mixed solvent of glycerol and deionized water at a ratio of 1:4 was prepared, and then 0.183% zinc chloride, 0.594% indium chloride tetrahydrate, and 0.501% thioacetamide (by mass percentage) were added sequentially. The mixture was magnetically stirred continuously for 0.5 h to obtain a homogeneous precursor dispersion. The prepared precursor dispersion was then reacted in an oil bath at 80 °C with stirring for 2 h to obtain a ZnIn2S4 catalyst suspension. The suspension was centrifuged for 0.5 h, and the bottom precipitate was collected. The precipitate was washed three times alternately with anhydrous ethanol and deionized water. The washed sample was then dried in a vacuum drying oven at 60 °C for 12 h to finally obtain the ZnIn2S4 catalyst.

[0040] Comparative Example 2: Preparation of WO3 composite material Ammonium metatungstate (4.5 g), lactic acid (8.75 g), and cysteine ​​(0.1383 g) were added to a 100 mL hydrothermal reactor containing ethanol (20 g), and the reaction was carried out at 180°C for 12 hours. After natural cooling to room temperature, the precipitate at the bottom was a hydrated tungsten oxide precursor. The precipitate was collected by centrifugation at 8000 r / min for 5 min; it was washed three times with deionized water and twice with ethanol. After drying, the precursor was calcined in a muffle furnace at 500°C for 2 h at a heating rate of 25°C·min. - ¹, WO3 composite material was prepared.

[0041] Structural characterization and performance testing Figure 1 The XRD patterns of the products prepared in Examples 1, 2, and 3 show that the diffraction signals of ZnIn2S4, WO3, and WS2 overlap in all products, and no impurity peaks were observed, indicating that the three-phase composite material has been successfully constructed. The peak at approximately 14.4° belongs to the (002) crystal plane of WS2. Multiple peaks in the range of 23–26° originate from the monoclinic structure of WO3, while the signals at 27.8° and 47.3° correspond to the (102) and (110) crystal planes of ZnIn2S4, respectively. The peak positions show almost no shift, indicating that each component retains its own lattice structure after composite formation, and no solid solution or phase transition has occurred.

[0042] Figure 2 The image shows a scanning electron microscope (SEM) image of the WO3 / WS2 carrier powder prepared in Example 1. As can be seen from the image, the ratio of WS2 to crystalline WO3 is balanced, forming a large-area tightly bonded heterogeneous interface. The WS2 sheets retain a complete two-dimensional structure, and nano-WO3 grains are uniformly grown on the surface without obvious sintering coarsening.

[0043] Figure 3 The image shows a scanning electron microscope (SEM) image of the ZnIn2S4 / WO3 / WS2 photocatalyst prepared in Example 1. As can be seen from the image, ZnIn2S4 nanosheets are uniformly and densely loaded on the surface of WO3 / WS2 nanosheets without large-scale accumulation or structural collapse, successfully constructing a tightly coupled heterojunction and effectively exposing the reactive surface. This unique layered composite structure is beneficial for shortening the charge transport distance and promoting interfacial interactions between different components.

[0044] Figure 4 The image shows the transmission spectrum of the ZnIn2S4 / WO3 / WS2 photocatalyst prepared in Example 1. The measured lattice spacing of 0.320 nm corresponds to the (102) crystal plane of hexagonal ZnIn2S4, the 0.388 nm lattice fringes highly match the (001) crystal plane of WO3, and the 0.273 nm lattice spacing belongs to the (101) crystal plane of WS2. All measured lattice parameters are in good agreement with standard XRD diffraction data, indicating that the heterostructure building process did not destroy the intrinsic crystal structure of each component, and each material maintained a complete and ordered crystalline state in the composite system. The clear crystal morphology and intact lattice structure endow this ternary composite material with excellent structural stability and good electrical conductivity. The ordered crystal structure effectively reduces defect density and carrier recombination centers, while the closely contacted heterostructure interface significantly accelerates the charge migration dynamics at the interface.

[0045] Figure 5 XPS spectra of the products prepared in Example 1 and the comparative examples are shown. The full-scan XPS spectrum of ZnIn2S4 / WO3 / WS2-300 shows characteristic signals of Zn, In, S, and W, confirming the successful recombination of WO3 / WS2 with ZnIn2S4. In the high-resolution S 2p spectrum, the original ZnIn2S4 exhibits S at 161.8 eV (S 2p 3 / 2) and 163.0 eV (S 2p 1 / 2). 2-The signal; while the S 2p peaks of WS2 are located at 161.4 eV and 162.6 eV. After constructing the heterojunction, all S 2p peaks of ZnIn2S4 / WO3 / WS2-300 shift towards higher binding energies, indicating a decrease in electron density around sulfur atoms and spontaneous electron transfer from ZnIn2S4 to WO3 / WS2 across the heterojunction interface. The O 1s peak of pure WO3 is located at 530.0 eV, attributed to O in the lattice. 2- Ions. When O in the WO3 / WS2 lattice 2- When ions gain electrons, their O 1s binding energy decreases; further loading with ZnIn2S4 further shifts the O 1s peak towards lower binding energies, increasing electron enrichment. Because oxygen in WO3 crystals is extremely electronegative, it can capture electrons from W... 6+ The transferred electrons ultimately make oxygen an electron aggregation site in the WO3 phase. For the W 4f spectrum, W in WS2... 4+ The peaks appeared at 32.4 eV (W 4f 7 / 2) and 34.5 eV (W 4f 5 / 2), respectively, while W in WO3... 6+ The signals appear at 36.1 eV and 38.2 eV. When combined with ZnIn2S4, the W in the WS2 phase... 4+ The binding energy shifts to higher values, indicating that tungsten continuously loses electrons; while in the WO3 phase, W... 6+ The binding energy shifts to lower values, indicating that tungsten continuously gains electrons. In summary, in WS2, tungsten acts as an electron donor (providing electrons...). - In WO3, tungsten acts as an electron acceptor (receiving electrons). - The introduction of ZnIn2S4 further enhances charge transfer. The Zn 2p peaks of pure ZnIn2S4 are located at 1022.1 eV (2p 3 / 2) and 1045.2 eV (2p 1 / 2), respectively, while in the ternary composite, these peaks shift by 0.3 eV towards higher binding energies. The 3d peaks of the original ZnIn2S4 are located at 444.6 eV (3d 5 / 2) and 452.2 eV (3d 3 / 2), respectively, shifting to 444.8 eV and 452.4 eV after hybridization. In the ternary heterostructure, both ZnIn2S4 and WS2 lose electrons, while WO3 gains electrons. This spontaneous charge redistribution creates a dual built-in electric field at the interface of ZnIn2S4, WO3, and WS2, effectively driving the separation of photogenerated carriers and suppressing intrinsic charge recombination.

[0046] The specific testing method for photocatalytic hydrogen production is as follows: All photocatalytic hydrogen production experiments were conducted in a 460 mL Pyrex glass reactor using a 300 W LED lamp (390-840 nm) as the light source, with a distance of 5 cm between the lamp and the reactor. 100 mL of 10% TEOA solution was poured into the glass reactor, followed by the addition of 20 mg of the prepared photocatalyst. The glass reactor was then installed in the recirculation system. The airtightness was checked, and the system was degassed for 30 min to remove air. A 300 W incandescent lamp equipped with an AM1.5G filter was used to illuminate the reactor to trigger the photocatalytic release of hydrogen. The generated gas was measured using an online gas chromatograph (GC-7979).

[0047] Figure 6 The graphs show the hydrogen production performance of the products prepared in each example and comparative example. It can be seen from the graphs that the original ZnIn2S4 and WS2 exhibit moderate photocatalytic hydrogen production performance, with hydrogen production rates of 630 μmol·g⁻¹, respectively. -1 ·h -1 and 420 μmol·g - ¹·h - ¹. The hydrogen evolution rates of ZnIn₂S₄ / WO₃ / WS₂-280, ZnIn₂S₄ / WO₃ / WS₂-300, and ZnIn₂S₄ / WO₃ / WS₂-320 were 1760, 2750, and 1440 μmol·g⁻¹, respectively. - ¹·h - ¹. Constructing a dual-built-in electric field ZnIn2S4 / WO3 / WS2 effective heterogeneous interface effectively optimizes charge separation and transport behavior at the interface. At the same time, the composite structure exposes abundant active sites to promote hydrogen reduction reaction, thereby significantly improving the utilization efficiency of incident photons and photogenerated charges.

[0048] Figure 7 The figure shows the cycling performance of the catalyst prepared in Example 1. As can be seen from the figure, after multiple cycles, the composite catalyst retained 92% of its initial photocatalytic activity, and no significant activity decay was observed in each cycle, demonstrating excellent structural and catalytic stability. This excellent cycling performance is attributed to the tightly bound heterojunction interface formed by moderate calcination. The strong interfacial interactions effectively inhibited the dissolution, stripping, and aggregation of active components during the long-term photocatalytic reaction, thereby maintaining intact charge transfer channels and preventing the loss of active sites and structural damage. This ensures stable and sustainable photocatalytic hydrogen production performance.

[0049] Figure 8 and 9The figures show the pore size distribution and specific surface area of ​​the catalysts prepared in Example 1 and the comparative example, respectively. The figures show that the catalysts have a mesoporous structure of 2-50 nm and a specific surface area of ​​131.997 m². 2 g -1 .

[0050] Figure 10 The images show the UV-Vis absorption spectra of the catalysts prepared in Example 1 and the comparative example. As can be seen from the images, the prepared ZnIn2S4 / WO3 / WS2 photocatalysts achieve continuous absorption of UV / short-wave visible light with an appropriate amount of crystallized WO3 and capture long-wave visible light with a sufficient amount of WS2. The ternary system achieves continuous absorption of a wide spectrum of 300~800 nm, maximizing the light energy capture efficiency.

[0051] Figure 11 The figures show the EIS spectra of the catalysts prepared in Example 1 and the comparative example. As can be seen from the figures, the ZnIn2S4 / WO3 / WS2-300 composite material has the smallest radius of curvature among all samples, indicating that the constructed ternary heterojunction effectively reduces the barrier to interfacial charge transfer and significantly accelerates the migration and transport of photogenerated carriers.

[0052] Figure 12 The figures show the PLS diagrams of the catalysts prepared in Example 1 and the comparative example. As can be seen from the figures, the ZnIn2S4 / WO3 / WS2-300 composite material exhibits a significant decrease in the PLS signal. This indicates that the well-structured heterojunction interface provides an efficient charge transfer channel, enabling rapid extraction and transfer of photoexcited charges, thereby effectively suppressing electron-hole recombination in the bulk phase and on the surface, and improving the utilization efficiency of photoexcited carriers.

[0053] Figure 13 The figures show the transient photocurrent of the catalysts prepared in Example 1 and the comparative example. As can be seen from the figures, the ZnIn2S4 / WO3 / WS2-300 composite material exhibits the highest and most stable transient photocurrent density during repeated light-on and light-off cycles. This ternary heterojunction structure effectively promotes the separation of photogenerated charges, maintains stable charge generation and migration performance, and provides a continuous and abundant active charge for the photocatalytic hydrogen evolution reaction, giving the composite catalyst excellent and long-lasting photocatalytic activity.

[0054] Figure 14This diagram illustrates the dual built-in electric fields and photoelectron directional transfer of the catalyst prepared in Example 1. Under dark conditions, the close contact between WO3, WS2, and ZnIn2S4 triggers spontaneous electron transfer: electrons migrate from ZnIn2S4 through interface I to WS2, and then from WS2 through interface II to WO3, until the Fermi levels of the three materials reach equilibrium and align with each other. During electron migration at the ZnIn2S4 / WS2 interface (interface I), ZnIn2S4 acts as an electron donor, losing electrons and forming a positively charged region near its surface. This process creates an electron-depleted layer on the ZnIn2S4 side, causing its band edge to bend upwards. Conversely, the adjacent WS2 surface receives and accumulates the migrated electrons, forming an electron-rich negatively charged layer, thereby causing the WS2 band edge to bend downwards. Therefore, an internal electric field I is established at the ZnIn2S4 / WS2 heterojunction. Similarly, the same electron transfer behavior and bandgap bending phenomenon are observed at the WS2 / WO3 heterojunction, ultimately forming an internal electric field II (interface II) at this interface. This creates a unidirectional electron transport path between WO3, WS2, and ZnIn2S4. Under illumination, WO3, WS2, and ZnIn2S4 all absorb energy, causing electrons in the valence band to transition from VB to CB and enter an excited state. Subsequently, under the influence of the internal electric field and Coulomb interaction, photogenerated electrons accumulate in the conduction bands of WO3 and WS2 and flow to the conduction band of ZnIn2S4, while photogenerated holes accumulate in WO3 and WS2. The coupling of the two built-in electric fields provides sufficient driving force for long-range photo-electron transfer, effectively achieving charge separation. The combination of the three materials forms a wider complementary light absorption window, thus significantly expanding the light utilization range and improving the photocatalytic hydrogen production performance.

[0055] Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields, characterized in that: It includes a layered WO3 / WS2 carrier and ZnIn2S4 loaded on the surface of the layered WO3 / WS2 carrier. The layered WO3 / WS2 carrier includes a layered WS2 substrate and WO3 formed in situ on the surface of the layered WS2 substrate.

2. The layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields according to claim 1, characterized in that: The mass fraction of ZnIn2S4 in the layered ZnIn2S4 / WO3 / WS2 composite material is 10%~50%.

3. The method for preparing layered ZnIn2S4 / WO3 / WS2 heterojunctions as described in claim 1 or 2, characterized in that, Includes the following steps: WS2 powder was heated to induce an oxidation reaction, resulting in a WO3 / WS2 support with WS2 as the substrate and WO3 forming on the surface. Glycerol and water were mixed to obtain a mixed solvent; the WO3 / WS2 carrier was added to the mixed solvent and ultrasonically dispersed to obtain a dispersion. Zinc salt, indium salt and thioacetamide were added to the dispersion and mixed thoroughly to obtain the precursor mixture. The precursor mixture was stirred and reacted at 75-90℃ for 1.5-3 hours to obtain a suspension. The precipitate in the suspension was separated, washed, and dried to obtain a layered ZnIn2S4 / WO3 / WS2 heterojunction with dual built-in electric fields.

4. The preparation method according to claim 3, characterized in that, The temperature at which the WS2 powder is heated to induce an oxidation reaction is 280~320℃.

5. The preparation method according to claim 3, characterized in that, The volume ratio of glycerol to water in the mixed solvent is 1:3 to 1:

5.

6. The preparation method according to claim 3, characterized in that, The amount of the WO3 / WS2 carrier added is 0.5% to 1.25% of the mass of the mixed solvent.

7. The preparation method according to claim 3, characterized in that, The zinc salt is zinc chloride; the indium salt is indium chloride tetrahydrate.

8. The preparation method according to claim 7, characterized in that, The amount of zinc chloride added is 0.15% to 0.20% of the mass of the mixed solvent; the amount of indium chloride tetrahydrate added is 0.20% to 0.80% of the mass of the mixed solvent; and the amount of thioacetamide added is 0.20% to 0.80% of the mass of the mixed solvent.

9. The preparation method according to claim 3, characterized in that, The washing method involves alternating between anhydrous ethanol and deionized water several times.

10. The layered ZnIn2S4 / WO3 / WS2 heterojunction as described in claim 1 or 2, or the layered ZnIn2S4 / WO3 / WS2 heterojunction prepared by the preparation method as described in any one of claims 3 to 9, is used as a catalyst for photocatalytic water splitting to produce hydrogen.